Considerações sobre alguns aspectos das práticas profissionais docentes, em contextos de mudanças curriculares - institucional - Vieira, Cibele Miranda (2010)
This research’s objective was to study the teaching practice in a working context permeated by the curricular renovation. It is composed of a case study with an ethnographic basis structured in a research performed by elementary school I teachers from a public school in the township of Maracanaú, located at Fortaleza’s metropolitan region in the state of Ceará. Observations were made mainly, but not exclusively, inside of the classrooms, as well as interviews with the participant teachers, school directors and central administration and documental analysis managers. The research’s results were organized according to the aspects of the teaching practice, like school planning, textbook use, formation actions, school schedules’ distribution and the research sources used by teachers in their planning. This study’s formulations allow the affirmation that the teachers’ position didn’t show meaningful changes that could be associated to the institutional change proposed. The analysis reveals that neither the teacher’s work is modified nor is it oriented to what is expected from them. The teaching work seems to already hold a previous formation which grows from the principles and experiences acquired through the teaching years and which resist the curricular and pedagogical changes. The change in teaching practice occurs at the moment in which he feels it is meaningful, in the sense that while there’s no meaning for it regarding the practice inside of the classroom, none of it will reach the school.